THE TWENTY-SECOND AMENDMENT TO THE US CONSTITUTION: A HISTORICAL AND LEGAL STUDY - Voronova, Izabella (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The Twenty-Second Amendment to the U.S. Constitution, adopted in 1951 in response to Franklin D. Roosevelt’s unprecedented four-term presidency, established a constitutional limit of two elected terms for the President. In the 21st century, this provision has once again become the focus of intense public and scholarly debate due to contemporary political and legal developments. Notably, in 2024, Donald Trump was elected to a second, non-consecutive presidential term—becoming the first president since Grover Cleveland to return to office after an interruption. This situation raised a number of questions regarding the scope of the amendment’s application and the potential circumvention of its prohibition on a third term. Additionally, in March 2025, a legislative initiative was introduced in the U.S. Congress aimed at amending the current limitation, thereby enabling Trump’s possible candidacy in the 2028 election. These developments, along with increasing calls to revise or repeal the amendment, pose a potential threat to the stability of the American constitutional system and underscore the relevance of a thorough legal analysis of the issue. The aim of the article is to conduct a historical and legal study of the Twenty-Second Amendment, focusing on its content, legal nature, and the practice of its interpretation and application. The research methodology combines general scientific, legal-specialized, and historical-legal methods. Summary of the main results of the study. The article examines the historical origins and political context of the amendment’s adoption, highlighting its structural nature, as opposed to other constitutional amendments that typically protect individual rights and freedoms. It introduces a new eligibility criterion—no more than two terms in the office of President. The article analyzes judicial interpretation and application of the amendment in U.S. case law and establishes that courts have not overturned decisions based on this provision, indicating consistent compliance with the constitutional norm. At the same time, the analysis emphasizes the potential conflict between literal and teleological interpretations: while the text of the amendment does not explicitly prohibit a non-consecutive third term, its spirit clearly aims to prevent prolonged presidential rule. The author argues that the amendment not only serves a restraining function but also significantly shapes the political dynamic of the presidency under the two-term limit. Conclusions. The Twenty-Second Amendment holds deep legal and political significance within the American constitutional framework. From a legal standpoint, it represents a rare case of restricting democratic choice in favor of republican principles: the amendment intentionally deprives the electorate of the option to elect the same individual for a third presidential term to prevent the excessive concentration of power. This constitutional compromise—historically justified—was designed to protect the republic from the dangers of prolonged personal rule. In practice, the amendment has largely achieved its intended purpose: since its adoption, regular presidential turnover has become a stable feature of U.S. governance, helping the country avoid scenarios of “elective monarchy” or indefinite leadership that often precipitate democratic crises elsewhere. The provision ensures periodic renewal of executive leadership, creating opportunities for new individuals and ideas to lead the nation. It has also affected the nature of the presidency by balancing the diminishing influence of second-term presidents with their enhanced freedom of action, unburdened by re-election prospects. The article concludes that the Twenty-Second Amendment serves as a vital stabilizing mechanism of American constitutionalism and, amid modern challenges, continues to perform its restraining role while remaining the subject of ongoing political and legal debate regarding its justification and future relevance.